Messenger ribonucleic acid abundance of intestinal enzymes and transporters in feed-restricted and refed chickens at different ages - Duarte, C. R. A. [UNESP]; Vicentini-Paulino, M. L. M. [UNESP]; Buratini, J. [UNESP]; Castilho, A. C. S. [UNESP]; Pinheiro, D. F. [UNESP] (Poultry Science Assoc Inc, 2011)
The effects of feed restriction and subsequent refeeding on the gene expression of intestinal enzymes and nutrient transporters at 2 ages, 7 and 35 d, were examined in different groups of broiler chickens. At each age, birds were feed restricted for 7 d (30% of ad libitum intake) followed by 3 d of refeeding ad libitum. Control groups were fed ad libitum. Total RNA of jejunal mucosa was extracted according to the Trizol protocol, and mRNA expression of sodium glucose transporter 1, glucose transporter 2, peptide transporter 1, aminopeptidase, maltase, and sucrase-isomaltase complex was obtained by reverse-transcription PCR. The expression of aminopeptidase, sodium glucose transporter 1, and peptide transporter 1 was higher in feed-restricted groups than in control groups at d 14 (181.4, 116.7, and 80.4%, respectively) and d 42 (143.5, 84.2, and 195.9%, respectively). The mRNA. abundance of sucrase-isomaltase complex was higher (159.1%) only in chickens that were feed restricted from d 35 to 42. No statistically significant effect of feed restriction was observed for mRNA abundance of maltase and glucose transporter 2 at either age. After refeeding (d 17 and 45), the RNA abundance of enzymes and nutrient transporters was similar to that in the control group. Thus, this study suggests that an effect of upregulation in gene expression exists during feed restriction that disappears when feed is supplied ad libitum.
Keywords: intestinal enzyme; intestinal transporter; feed restriction; refeeding; gene expression